2021
DOI: 10.21203/rs.3.rs-923871/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social Isolation Induces Neuroinflammation And Microglia Overactivation, While Dihydromyricetin Prevents And Improves Them.

Abstract: Background: Anxiety disorders are the most prevalent mental illnesses in the U.S. and are estimated to consume one-third of the country's mental health treatment cost. Although anxiolytic therapies are available, many patients still exhibit treatment-resistance, relapse, or substantial side effects. Further, due to the COVID-19 pandemic and stay-at-home order, social isolation, fear of the pandemic, and unprecedented times, the incidence of anxiety has dramatically increased. Previously, we have demonstrated d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
3
1
Order By: Relevance
“…In contrast to Al-Omam et al (2022) , this study observed increased microglial count in the three brain regions of isolated male mice. Our finding is supported by a meta-analysis study that found an increase in microglia count in postmortem brains of patients with schizophrenia ( van Kesteren et al, 2017 ).…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…In contrast to Al-Omam et al (2022) , this study observed increased microglial count in the three brain regions of isolated male mice. Our finding is supported by a meta-analysis study that found an increase in microglia count in postmortem brains of patients with schizophrenia ( van Kesteren et al, 2017 ).…”
Section: Discussioncontrasting
confidence: 95%
“…This study revealed that social isolation led to increased locomotor activity, depression, anxiety, and impaired prepulse inhibition function. Previous studies have shown these impairments ( Al Oman et al, 2022 ; Lander et al, 2017 ). Hence, social isolation used in this study was able to induce schizophrenia-related behaviours in both male and female mice.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Neuroinflammation is a definite immunological concomitant of the psychosocial problems inflicted by social isolation. In a study on eight-week-old male C57BL/6 mice, Al Omran et al showed that social isolation resulted in microglial activation and the release of pro-inflammatory cytokines [153]. Analogously, in a study with BALB/c mice, Ayilara and Owoyele demonstrated evidence of neuroinflammation manifesting as increased activated microglial count and elevated IL-1β and TNFα cytokine levels in a social isolation rearing model [154].…”
Section: Social Isolationmentioning
confidence: 97%